An Extended Position Based Dynamics Method for Cloth Simulation. (May 2020) - Quan, Wei; Teng, Dexin; Li, Hua; Han, Cheng
Abstract: Position based dynamics is an effective method in real time deformable body simulation, which is widely used. But, as we all know, it is not suitable for greater accuracy applications. As to cloth simulation, the over-stretching problem especially affects its accuracy. Therefore, an extended simulation method based on position dynamics is proposed in this paper. The time step is subdivided effectively, and the number of iterations is controlled when cloth is deforming; We also optimize the Gauss-Seidel iterative solver in parallel using an improved grouping method which ensures the efficiency of the algorithm. This method is simple and easy to implement. Compared with the traditional method, the position error of deformation is significantly reduced while cloth is stretched, and the simulation efficiency is enhanced. Besides, it can be easily integrated into the existing position based dynamic framework.